DIGITAL MAP APPLICATION FOR SUPERMARKET - Luftia Nora; Jurnalis J. Hius (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
Digital map is consisted of a number of files that used to be applied as the basis elements, like dots, lines and space, in making a map. Each of those elements has been marked according to its administrative code area stored in a computer. The objective of this paper is to design an application for goods placement in supermarkets based on website, thus make the costumers easier in finding location of goods they wish to buy. This research used direct interview and observation method in a supermarket and its employees. With the facility given to the admin and user, it enables them to use this system properly according to their needs.  This system is designed by marking the coordinates of all available racks in the supermarket which are have their own specific information. This application is run well with additional features like searching goods and searching goods based on its type.Keywords: Digital map, supermarket